Extract of Beluntas (Pluchea indica) as an Antibacterial Towards Streptococcus mutans ATCC 25175 Causes of Dental Carries - Nurrohman, Endrik; Pantiwati, Yuni; Susetyarini, Eko; Umami, Erika Khoirul (BIO-EDU: Jurnal Pendidikan Biologi, 2021)
Abstract The purpose of this study is to analyze the antibacterial activity of various concentrations of beluntas leaf extract by examining the inhibition zone’s diameter of Streptococcus mutans ATCC 25175 bacteria. This type of research is experimental. The research was conducted at the Chemical Engineering Laboratory of State Polytechnic of Malang and the Biology Laboratory of the University of Muhammadiyah Malang. The study was conducted from October to December 2020. The research design used a completely randomized design (CRD) with 7 treatments and 3 replications. The standard of turbidity of bacterial isolates used Mcferland 108. Research design was Posttest-Only Control Design. Data analysis used one-way ANOVA and Duncan's continued test of 5%. The results showed that there was an effect of giving various concentrations of beluntas leaf extract on the inhibition zone of Streptococcus mutans bacteria. The results of Duncan's analysis showed that the concentration of 25% had the most significant effect compared to other treatments and was significantly different from other treatments but rather far from the positive control treatment result. The findings of this study is the content of active compounds in beluntas leaves have an effect as antibacterial towards Streptococcus mutans, also, at a concentration of 5% with minimum inhibitory concentration (khm).